2023
DOI: 10.32604/or.2023.029414
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the clinical and immunological value of m6A regulator-mediated methylation modification patterns in adrenocortical carcinoma

Abstract: N6-methyladenosine methylation (m6A) is a common type of epigenetic alteration that prominently affects the prognosis of tumor patients. However, it is unknown how the m6A regulator affects the tumor microenvironment (TME) cell infiltration in adrenocortical carcinoma (ACC) and how it affects the prognosis of ACC patients yet. The m6A alteration patterns of 112 ACC patients were evaluated, furthermore, the association with immune infiltration cell features was investigated. The unsupervised clustering method w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…According to earlier studies, the down-regulation of the SF3A1 gene is associated with Paget's disease of bone (PDB) [40]. The protein encoded by the ATXN2L gene belongs to the spinocerebellar ataxia (SCAs) family, which is mainly associated with neurodegenerative disorders [41,42]. To the best of our knowledge, the role of this gene has not been explored in OP so far, we are the first to report the down-regulation of this gene in OP patients.…”
Section: Discussionmentioning
confidence: 99%
“…According to earlier studies, the down-regulation of the SF3A1 gene is associated with Paget's disease of bone (PDB) [40]. The protein encoded by the ATXN2L gene belongs to the spinocerebellar ataxia (SCAs) family, which is mainly associated with neurodegenerative disorders [41,42]. To the best of our knowledge, the role of this gene has not been explored in OP so far, we are the first to report the down-regulation of this gene in OP patients.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21] In addition, m6A affects tumour expression, immunotherapy, and targeted therapy by altering programmed cell death, metabolism, drug resistance, and oncogenes. 22,23 Here, to further verify the targeted relationship between METTL14 and SOX4, this study used RIP and MeRIP-qPCR to demonstrate that m6A-modified SOX4 was the downstream target of METTL14. The experimental findings revealed that METTL14 exerts a negative regulatory effect on SOX4 expression, with SOX4 expression being modulated by METTL14-mediated m6A methylation.…”
Section: Discussionmentioning
confidence: 99%
“…STRING (Search Tool for the Retrieval of Interacting Genes/Proteins) is a comprehensive database that facilitates the exploration of protein-protein interactions [26,27]. It integrates diverse interaction sources, including experimental data and computational predictions, offering a holistic view of the interactome landscape.…”
Section: String and Gene Enrichment Analysesmentioning
confidence: 99%